Organization development as instrument to build and maintain organizational effectiveness in remote mode: a qualitative inductive research - Autenrieth, Laura Christin (2022)
The public-health driven COVID-19 lockdowns unpredictably forced organization development (OD) consultants to work from home in no time. As original interventions, driven by behavioral and social science knowledge were predominantly designed for face-to-face encounters, adaptation to virtual OD services was inevitable. The purpose of this study was to investigate how organization development consultants adjusted their labor activity from a predominantly face-to-face to a solely technology-mediated setting. We adopted a bottom-up, research approach to inductive concept development, following Gioia and colleagues’ methodology (2013) to study the adaptation process of 10 both external and internal OD consultants. The emergent framework suggests that adjusting to a virtual setting was a complex process that occurs in more or less sequential stages: (1) we go into action, (2) acknowledging limits, (3) an ongoing need and evolvement of a tech & tool literacy, and finally (4) the acceptance of change, resulting in an evolved state of the occupational field. The findings indicate a parallel to Lewin’s famous Three-Phase Model of Change (1951). We suggest that our emergent framework can be well applied by other occupational fields (e.g., education sector, therapy, consultancies) in a transition process to a virtual setting. To facilitate the transition in other occupational fields we outline a roadmap as guidance.